Suckling calves (Bos taurus) with pica exhibit blood metabolome alterations - CHEN, L; ZHANG, J; LI, N; ZHANG, L; XU, X F (Indian journal of animal sciences, 2020)
The aim of this study was to evaluate the changes of blood metabolomics in calves with pica, which causes serious harm to livestock. Two groups, each comprising 12 calves of approximately 3 weeks old and of similar weight were selected as subjects; Group A calves were control animals in good condition and Group B calves (pica animals) had rough hair, emaciation, flaccid forestomach, diarrhoea, and stunted development. Blood samples were collected from the tail root vein. Masslynx 4.1 software (Waters Company) was used to pre-process data, which were then analysed by principal component analysis, partial least squares discriminant analysis, and orthogonal partial least squares discriminant analysis. Twenty potential biomarkers were closely related to the occurrence of pica, viz. GDP-glucose, UDP-glucose, proline, creatine, arginine, glutamine, citrulline, urea, alanine, methionine, serine, glycerate, cysteine, spermine, spermidine, carnitine, xanthurenic acid, kynurenine, and thyroxine. Metabolic pathway analysis showed that, in calves, pica resulted in decreased antioxidant capacity; disruption of the mutual transformation between pentose and glucuronic acid; abnormal metabolism of cysteine, methionine, serine, arginine, and proline; impairment of lipid metabolism; reduced immunity; increased intestinal permeability; and elevated central nervous excitability. Calves with pica exhibit disruption of various metabolic pathways.